Fractal version of hyper-Wiener index. (January 2023) - Lu, Ying; Xu, Jiajun; Xi, Lifeng
Abstract: We propose the Fractal version of the hyper-Wiener index and we calculate the hyper-Wiener index on the Sierpiński gasket, a classical self-similar fractal, by developing the notion of pattern introduced by S. Wang et al (2017).